On the Rationality of Forecasts - Lee, Bong-Soo (The Review of Economics and Statistics, 1991)
This paper discusses a method of deriving the univariate ARIMA process followed by a time series of rational forecasts y(superscript "e") of a series y, given the ARIMA process followed by y. The method suggests examination of the empirical ARIMA process followed by y(superscript "e") as a test of the hypothesis that y(superscript "e") is a rational forecast of y in a strong sense. The method is applied to a measure of expected inflation: the survey data conducted by Money Market Service, Inc., of money market participants. Copyright 1991 by MIT Press.